EXPLORING ORAL LANGUAGE ASSESSMENT PRACTICE OF AN EFL TEACHER IN AN INDONESIAN SECONDARY SCHOOL: A QUALITATIVE CASE STUDY - Nurismi; Nur Hidayanto Pancoro Setyo Putro (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2026)
Oral language assessment plays an important role in evaluating the speaking competence of learners in English as a Foreign Language (EFL) classrooms. Although previous studies have examined the effectiveness of oral assessment techniques in supporting language learning, limited research has explored how teachers implement oral language assessment and make assessment decisions in authentic classroom contexts, particularly in Indonesian secondary schools. This qualitative case study investigated the oral language assessment practices of a senior high school English teacher teaching Grade XI learners in Yogyakarta, Indonesia. Semi-structured interviews, classroom observations, and document analysis were used to collect data and were analysed using thematic analysis. The findings revealed that the teacher primarily employed role-play dialogues and group discussions as oral assessment strategies because these activities facilitated authentic communication while enabling the assessment of pronunciation, fluency, vocabulary, and grammatical accuracy. The findings also indicated that assessment practices were shaped by contextual factors, including time constraints, varying proficiency levels, and the need for flexible assessment criteria. Furthermore, oral assessment was perceived as supporting the participation and engagement of learning during speaking activities. This study contributes to participation and engagement during speaking activities. This study contributes to the literature on classroom-based oral assessment by highlighting the influence of contextual factors on teachers’ assessment decisions and emphasizing the importance of teacher assessment literacy in implementing effective oral language assessment practices.